Profile of Leachate and Sea Water in The Waste Processing Area Suwung, Denpasar, Bali - Iswari, Pande Kadek Ari; Ernawati, Ni Made; Restu, I Wayan (Advances in Tropical Biodiversity and Environmental Sciences, 2021)
This study aims to determine the profile of leachate, and seawater in the Suwung waste processing area (TPA Suwung). The method used in this research was descriptive quantitative. The results showed a high profile of untreated leachate with a TSS value of 9.407 mg/L, pH with a value of 8.17, DO with a value of 0.063 mg/L, BOD with a value of 375.5 mg/L, and COD with a value of 5.776 mg/L. The treated leachate with a TSS value of 4,987 mg/L, pH with a value of 8.52, DO with a value of 0.063 mg/L, BOD with a value of 321.9 mg/L, and a COD value with a value of 3.069 mg/L. Meanwhile, the seawater profile was classified as good with parameter values of TSS with a value of 76 mg/L, DO 7.54 mg/L, pH 7.54, BOD with a value of 13.6 mg/L, COD with a value of 64 mg/L. The existence of TPA Suwung has a negative impact and influence on seawater in the area. Revitalization efforts are needed to carry out leachate water treatment so that the effluent quality can be improved for the quality of water around TPA Suwung.